2021
DOI: 10.1186/s12969-021-00495-4
|View full text |Cite
|
Sign up to set email alerts
|

I don’t want to think about it: a qualitative study of children (6–18 years) with rheumatic diseases and parents’ experiences with regular needle injections at home

Abstract: Background Overall outcomes of pediatric rheumatic diseases (RD) have improved due to treatment with biologic agents and methotrexate. For many children, this treatment often entails regular needle injections. Pain and fear of needle injections are common in childhood, but how children and parents handle long-term needle injections at home has not been fully explored. This study aimed to explore how regular needle injections affect children with RD and their parents in their daily living. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…Unfortunately, mothers in this study reported receiving minimal support regarding their child's treatments. Although it seemed that emotional responses tended to improve with habituation, confidence, and knowledge with treatments, which would be consistent with other literature (20,28), it is important that parents receive psychosocial support early on and throughout these processes, as emotions can change with the disease course (42). While parents have been included in psychosocial interventions in JIA (e.g., 29), they have rarely been the focus, and there is a clear need for more evidence-based interventions geared toward them.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Unfortunately, mothers in this study reported receiving minimal support regarding their child's treatments. Although it seemed that emotional responses tended to improve with habituation, confidence, and knowledge with treatments, which would be consistent with other literature (20,28), it is important that parents receive psychosocial support early on and throughout these processes, as emotions can change with the disease course (42). While parents have been included in psychosocial interventions in JIA (e.g., 29), they have rarely been the focus, and there is a clear need for more evidence-based interventions geared toward them.…”
Section: Discussionsupporting
confidence: 91%
“…Another key implication of this study is the importance of supporting mothers through these treatments, decisions, and transitions of care not only for their own well‐being, but for the health of their child (49). Based on the results of this study, it is recommended that health care providers check in with mothers regularly with regard to their experiences with their child's treatments and support them either through treatment‐specific education and training (10,26,28), referrals to JIA communities for social support (34,50), or referrals to evidence‐based psychological therapies to manage their child's treatment pain or the mother's own mental health (29–31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Childhood Arthritis Rheumatology Research Alliance (CARRA) survey the physicians’ attitudes towards tapering in sJIA were assessed; 39% preferred tapering biological treatment over 2–6 months and favoured interval prolongation [ 37 ]. Particularly for children, interval prolongation often increases quality of life due to a reduced hospitalization rate for infusions or decreased frequency of s.c injections, which are often associated with discomfort, fear and worries [ 38 ]. Furthermore, interval prolongation may result in lower drug costs, as absolute treatment doses needed in childhood are commonly lower than those offered in the adult-dose vial, resulting in expensive drug discharge with every injection.…”
Section: Discussionmentioning
confidence: 99%
“…A corto plazo, el manejo inadecuado del dolor provoca estrés, ansiedad, prolongación de estancias hospitalarias y aumento de costos 6 , mientras que a largo plazo ocasiona hiperalgesia, rechazo a los establecimientos de salud 7 y estrés postraumático 8 , ocasionando una reducción a la adherencia en los tratamientos crónicos 9 .…”
Section: Non-pharmacological Strategies As Adjuvants In Needle Associ...unclassified